PEMBERDAYAAN MASYARAKAT PETANI MADU HUTAN OLEH BALAI PENGELOLAAN DAERAH ALIRAN SUNGAI DAN HUTAN LINDUNG (BPDASHL) INDRAGIRI ROKAN DI DESA SAHILAN DARUSSALAM KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - Pratama, Jaya; Tua R.F.S, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Empowerment has been given by BPDASHL Indragiri Rokan to sailan honey farmer group, but sailan honey farmer group has not been independent because of the limited technology supporting production, capital, the existence of forest destruction, and lack of adequate marketing facilities. The theory used in this research is empowerment according to Winarni (1998:75), namely: (1) enabling, which includes motivating and awakening consciousness; (2) empowering, which includes education or knowledge, health, capital, technology, information, employment, markets; and (3) the creation of independence. This research uses qualitative method with descriptive research type. Data collecting technique used is interview technique, observation, and documentation. The result of the research can be concluded that: (1) empowerment of forest honey farmer community by Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung (BPDASHL) Indragiri Rokan in Sahilan Darussalam Village, Gunung Sahilan Sub-District of Kampar Regency has not been optimal. Especially the aspect of empowering and the aspect of self-reliance. The empowering aspect has not been optimal because of the lack of attention to the level of knowlage of the farmer group in managging forest honey, paying less attention to the farmer group health, lack of appropriate technology aid, and lack of capital aid. So the aspect of creating self-sufficiently has not been optimal. (2) the inhibiting factors of the empowerment of forest honey farmers by Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung (BPDASHL) Indragiri Rokan in Sahilan Darussalam Village, Gunung Sahilan sub-district, Kampar Regency are factors: (a) budget or funding; (b) there are still many people who have not been incorporated into farmer group; (c) lack of appropriate technology; and (d) illegal logging.Keywords : Empowerment, Honey Farmer, Forest